Work-related stress and its associated factors among primary care doctors in Malaysia during the COVID-19 pandemic - Muhammad Shah Shahrudin; Nik Munirah Nik-Nasir; Mohamed-Syarif Mohamed-Yassin (BMC Primary Care)
Abstract Background In Malaysia, the recent COVID-19 pandemic had increased the workload of all health professionals, especially primary care doctors (PCDs). Hence, this study aimed to determine the level of work-related stress and factors associated with higher levels of work-related stress among PCDs in Malaysia during this pandemic. Methods A cross-sectional study was conducted online using Google Forms™. Sociodemographic as well as work and workplace data were collected. The Job Demand Inventory, Physicians’ Lack of Professional Autonomy, and Health Professions Stress Inventory questionnaires were used to assess the job demand score, job autonomy score, and the level of work-related stress, respectively. Multiple linear regression was performed to determine the significant factors associated with higher work-related stress. Results A total of 301 PCDs participated in this study with the majority being female (76.1%), Malay (67.8%), married (73.1%), medical officers (68.8%), and worked in urban (70.4%) and public primary care clinics (83%). The mean (SD) score for work-related stress was 62.8 (18.4), (score range 0-120). PCDs who had any degree of worry about being alienated by friends and relatives because of close contact with COVID-19 patients had higher work-related stress levels compared to PCDs who did not have any worry [rarely (b = 10.23, 95% CI:5.57, 14.89), sometimes (b = 10.41, 95% CI:5.68, 15.13), often (b = 10.12, 95% CI:4.16, 16.08), and always (b = 14.65, 95% CI:7.43, 21.89)]. The other significant factor was higher job demand scores (b = 1.13, 95% CI:0.91, 1.35). In contrast, PCDs who always received support from supervisors at their workplace were found to have lower work-related stress levels compared to those who did not receive any support (b=-5.65, 95% CI:-10.38, -0.93). Conclusions The level of work-related stress among Malaysian PCDs during the COVID-19 pandemic was higher compared to American PCDs and Malaysian physicians before the pandemic but lower compared to Australian emergency physicians during the pandemic. Urgent measures to address the above-mentioned associated factors should be implemented as another pandemic may be just around the corner.